Analisis Pengaruh Faktor Penjadwalan Kapal, Jasa Pemanduan, Produktivitas Bongkar Muat Terhadap Waiting Time Kapal - Negara, Gembong Satria; Weda, Iwan; Syabani, Muhammad Fadzli (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Ship waiting time is one issue that is always getting serious attention in every country. Marine transportation became the main made of transportation in trade. Nearly 90% of foreign trade is done by sea. Freight carried by sea to be very efficient due to large carring capacity and this the role of the port as a place where ships can carry out loading and unloading of goods becomes an important means of supporting adequate facilities and infrastructure. If the performance of the port is not optimal, it will have a direct impact on the service so that it will cause new problems, namely the ship’s waiting time gets higher, so that it willlead to high costs, which have a direct impact on the price of goods on the market. This research has objective to know analysis the influence of factor ship scheduling, pilotage, and loading and unloading productivity to the waiting time. This research was conducted at the Port of Sei Kolak Kijang as a sample. The data collection done was through a method of observation, the literature study, interview, documentatuion and the questionnaires. Techique the analysis used is linear regression multiple with program assitance SPSS V.20. Based on the results of research and analysis produced equation: Y = 15.326 - 0,220 X1 - 0,178 X2 – 0,308 X3 + µ. Where the decision variable of waiting time (Y), ship scheduling (X1), pilotage (X2), loading and unloading productivity (X3) tested using t test show that the three independent variables significantly influence passenger decision as dependent variable. The Adjusted R Square number of 0,665 indicates that 66,5 percent of waiting time variables can be explained through the three independent variables in the regression equation. While the remaining 33,5 percent is explained by other variables outside the three variables used in this study.